ФОРМУВАННЯ ЕСТЕТИЧНОГО СМАКУ ЯК ВАЖЛИВА СКЛАДОВА МИСТЕЦЬКО-ПЕДАГОГІЧНОЇ ОСВІТИ (Педагогіка вищої та середньої школи, 2007)
The questions of formation of aesthetic taste as an important component of art-pedagogical education based on the main points of the monograph by N. Kalashnik «Aesthetic tastes: their cources andformation».